2012
DOI: 10.1007/s10067-012-2053-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight reduction on the quality of life in obese patients with fibromyalgia syndrome: a randomized controlled trial

Abstract: The aim of the study was to examine whether weight reduction can result in improvement of fibromyalgia impact questionnaire (FIQ) in the patients with fibromyalgia syndrome (FMS). This study was a randomized controlled trial. Obese patients with fibromyalgia were randomly assigned to 6-month dietary weight loss (n = 41) and no weight loss (n = 42) groups. Patients were assessed at baseline and at 6 months. The primary outcome measure was FIQ. Secondary measures included the tender point (TP) examination, Beck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 40 publications
2
107
0
4
Order By: Relevance
“…Similar correlations have emerged in FMS patients [590,591]. There is growing evidence that weight loss may be an important component of the treatment of FMS patients and can be associated with significant improvements in overall symptom severity, pain, depression, and HRQoL [443,590].…”
Section: Treatment and Outcome Treatmentmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar correlations have emerged in FMS patients [590,591]. There is growing evidence that weight loss may be an important component of the treatment of FMS patients and can be associated with significant improvements in overall symptom severity, pain, depression, and HRQoL [443,590].…”
Section: Treatment and Outcome Treatmentmentioning
confidence: 78%
“…There are a variety of potential confounders that were not given enough consideration in most studies. These include depression and anxiety [425,441], comorbid CFS [426], pre-or post-menopausal status [433]; and BMI [442,443]. In addition, the testing of TPs is stressful for patients with FMS and may be associated with a prolonged rise in cytokine production [340], and therefore should not be undertaken on the same day as blood draws for the measurement of basal hormone or cytokine levels.…”
Section: Cytokinesmentioning
confidence: 99%
“…Weight loss has been found to be associated with reduced levels of systemic pro-inflammatory markers in pain conditions including fibromyalgia syndrome [47], low back pain [48,49] and osteoarthritis of the knee [6,7,46,50]. It has also been found that bariatric surgery has a positive effect on musculoskeletal pain outcomes by reducing the long-term risk of developing work-restricting musculoskeletal pain and increasing the likelihood of recovering from such pain.…”
Section: Chronic Musculoskeletal Pain and Obesitymentioning
confidence: 93%
“…A number of studies have shown that weight loss reduces the levels of pro-inflammatory markers and that even a modest weight loss will have benefits in terms of decreased pain and pain-related problems such as depression, sleep disturbance, fatigue and mechanical overload [7,47,49,50,58,59].…”
Section: The Role Of Physical Activity In Reducing Obesity-related Cmentioning
confidence: 99%
“…Consumption of foods rich in carbohydrate that result in postprandial elevation in blood glucose cause repetitive acute inflammation that can worsen systemic inflammation [11]. Research suggests that weight loss reduces the levels of proinflammatory markers in fibromyalgia [12], low back pain [13] and osteoarthritis of the knee [4]. It has also been claimed that exercise itself has a prophylactic effect on the development of some pain conditions such as fibromyalgia syndrome, and neck, shoulder and back pain [14].…”
Section: The Role Of Exercisementioning
confidence: 99%